PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL ACTIVITY OF TENGKAWANG BUKIT (Shorea beccariana) STEM EXTRACT AGAINST Vibrio parahaemolyticus - Anisa, Hosia; Mukti, Akhmad Taufiq; Mahasri, Gunanti; Amin, Muhamad; Aminah, Nanik Siti (Jurnal Riset Akuakultur, 2025)
Vibrio parahaemolyticus infection poses a significant challenge in intensive shrimp culture, leading to substantial economic losses. Its common treatments using synthetic antibiotics have been linked to increased risks of antibiotic resistance and residual effects. Therefore, finding environmentally safe and effective natural alternatives is deemed essential. Tengkawang Bukit (Shorea beccariana) stem extract contains antibacterial compounds, including asiatic acid, oleanolic acid, and lupanone, all classified as terpenoids. This study aims to evaluate the antibacterial potential of S. beccariana stem extract through phytochemical screening and a disc diffusion test against V. parahaemolyticus. The screening results confirmed the presence of bioactive compounds, including alkaloids, flavonoids, saponins, tannins, and steroids. The disc diffusion test showed an increase in the inhibition zone with increasing extract concentration, with inhibition diameters ranging from 9.04 ± 0.48 mm to 10.75 ± 0.26 mm. The 17% extract yield indicates a high availability of active compounds. These findings suggest that tengkawang bukit stem extract has potential as a natural antibacterial alternative for controlling V. parahaemolyticus in shrimp culture. This approach could help reduce reliance on synthetic antibiotics and promote sustainable fisheries. Infeksi Vibrio parahaemolyticus merupakan salah satu kendala utama dalam budidaya udang yang menyebabkan kerugian ekonomi signifikan. Penggunaan antibiotik sintetis sebagai pengobatan telah menimbulkan kekhawatiran terkait resistensi dan residu, sehingga diperlukan alternatif alami yang aman dan efektif. Batang tengkawang bukit (Shorea beccariana) diketahui mengandung senyawa antibakteri seperti asam asiatik, asam oleanolik, dan lupanon yang tergolong ke dalam senyawa terpenoid. Studi ini bertujuan untuk mengevaluasi potensi antibakteri ekstrak batang S. beccariana melalui skrining fitokimia dan uji difusi cakram terhadap V. parahaemolyticus. Hasil skrining menunjukkan adanya kandungan senyawa bioaktif berupa alkaloid, flavonoid, saponin, tanin, dan steroid. Uji difusi cakram memperlihatkan zona hambat yang meningkat seiring dengan peningkatan konsentrasi ekstrak, dengan diameter hambatan berkisar 9,04 ± 0,48 mm hingga 10,75 ± 0,26 mm. Rendemen ekstrak sebesar 17% menunjukkan ketersediaan senyawa aktif yang melimpah. Hasil riset ini mengindikasikan bahwa ekstrak batang tengkawang bukit berpotensi sebagai alternatif antibakteri alami dalam pengendalian V. parahaemolyticus pada budidaya udang, sehingga dapat mengurangi ketergantungan terhadap antibiotik sintetis dan mendukung keberlanjutan perikanan.